Human placental androgen receptor variants: Potential regulators of male fetal growth. (May 2019) - Meakin, Ashley S.; Saif, Zarqa; Tuck, Astrud R.; Clifton, Vicki L.
Abstract: Introduction: Numerous studies show that males have increased intrauterine growth compared to females, and that pregnancy complications may further these growth differences, but the regulatory mechanisms underlying these differences remain unknown. We propose that these growth outcomes may be due to sex-specific differences in androgen sensitivity – giving rise to altered growth signalling pathways – mediated by the differential expression of placental androgen receptor (AR) variants. Methods: Placental protein and mRNA were used to identify AR protein variant levels and AR-downstream target gene expression, and were then analysed against neonatal measurements. Dihydrotestosterone (DHT)-induced AR protein variant expression and downstream growth factors were examined in vitro . Results: Four known AR variants (AR-FL, AR-V1, AR-V7, and AR-45), and three unknown proteins (120, 90 and 55 kDa) immunoreactive to the anti-AR antibody were identified in human placentae. Male placentae from controlled asthmatic pregnancies had increased AR-45 and decreased AR-V1 and AR-V7 nuclear expression. Increased nuclear AR-45 expression was associated with increased insulin-like growth factor 1 ( IGF-1 ), IGF-1 receptor ( IGF-1R ), and IGF-binding protein 5 ( IGFBP-5 ) mRNA expression and normal male growth. AR-45 mRNA and protein did not change in the presence of uncontrolled maternal asthma and associated with an increase in small for gestational (SGA) male fetuses. In vitro DHT stimulation increased AR-45 protein and IGF-1R and IGFBP- 5 mRNA expression. Conclusions: Collectively, our data shows altered AR protein expression and downstream signalling targets may contribute to sex-specific fetal growth outcomes in response to an adverse environment, and that AR-45 appears central in mediating these changes. Highlights: Multiple AR variants identified in the human placenta for the first time. AR-45 expression altered in only male placentae from asthmatic pregnancies. AR-45 correlated with androgen-induced growth factors in only male placentae. AR-45 may regulate male growth under adverse pregnancy conditions.